Basic statistics for business & economics - Lind Douglas A; Marchal William G; Wathen Samuel A (Boston McGraw-Hill, 2006)
Basic Statistics for Business and Economics 5e is a derivative of the best-selling STATISTICAL TECHNIQUES IN BUSINESS AND ECONOMICS, 12/e offering the essential topics of statistical tools and methods delivered in a student friendly, step-by-step format.
Accompanies a CD-ROM bearing acc no D677
Keywords: Statistics-theory and methods